Characteristics of Patients with Positive Cervical Cancer Screening using Visual Inspection with Acetic Acid (VIA) in Bantul District 2023: A Descriptive Study - Firdaus, Muhammad Reza; Rohmah, Nilna Sa'adatar; Aryanto, Samsu; Wiratama, Bayu Satria (Universitas Teuku Umar, 2025)
Background: Cervical cancer is the second leading cause of death in Indonesia and is one of the largest burdens on health costs. This study aims to determine the distribution of characteristics of positive cervical cancer screening patients in the Bantul District. Method: A descriptive study using data from cervical cancer screening reports at Bantul District Health Office in 2023 was conducted to observe treatment outcomes, demographic factors (education, age, working status, marital status, and address), nutritional status, and behavior. Cervical cancer screening was done using Visual Inspection with Acetic Acid (VIA). Proportions were calculated for univariate analysis. Results: There were 1,587 females screened and 40 people (2,5%) were positive. Among those positive cases, only 7.5% received cryotherapy and 55% were referred to other health centers (either primary centers with cryotherapy facilities or secondary centers for further treatment). Most of positive cases married (25/25; 100%), non-drinker of alcohol (25/25; 100%), non-smoker (25/25; 100%), had high education levels (17/23; 73.9%), overweight (15/22; 68.2%), 20-44 years old (26/40; 65%), were not working (16/25; 64%), did not regularly consume fruits and vegetables (16/25; 64%), and active physical activity (13/25; 52%). There were variables with missing data ranging from 37.5% to 45%, with the variable that had the most missing data being BMI, while the variable with the most complete data was age. The positive cases were distributed across 9 sub-districts (52,9%). Conclusion: The majority of positive cases were married, non-drinkers of alcohol, non-smokers, higher education levels, overweight, 20-44 years old, not working, unhealthy dietary habits, active physical activity, and 37.5% unknown follow-up. These findings underline the need for targeted interventions to improve follow-up care and conduct follow-up studies regarding risk factors of cervical cancer.